Activities in Iberoamerica of the Iberoamerican Network of Toxicology and Chemical Safety - de la Peña, E.; Herrero, Ó. (Spanish Journal of Environmental Mutagenesis and Genomics, 2025)
Our research activity focuses on mutagenic evaluation studies, including carcinogenic evolution through assays with Salmonella/microsomal and with cell cultures, using human peripheral blood lymphocytes and in vitro cell lines, evaluating natural and synthetic products, mainly for phytosanitary use and as a cytostatic agent. In the poster, we show the close collaboration between the Environmental Mutagenesis Group of the CSIC and the members of the Toxicological Centers of Mexico, under the direction of the Toxicological Center of the Juárez Hospital of Mexico and the Toxicological Center of Ángel Hospital of Morelia, and with the Chilean Universities of Valparaíso, the University of Concepción, the Catholic University of the North in Coquimbo, the University of Antofagasta, Andrés Bello University, and RITA-Chile. RITSQ was created by a joint initiative of the University of São Paulo, a member of IUTOX, and the President of the Spanish Association of Toxicology of the Spanish National Research Council. Its activities began in 2006, and since then, we have held RITSQ meetings in 2007 in Montreal, Canada; in 2010 in Barcelona, Spain; in 2016 in Mérida, Mexico; and in 2024 in Santiago de Chile, Chile. RITSQ is part of the sister organizations of the Hispanic Organization of Toxicologists (HOT) of the Society of Toxicology (SOT). In the eighteen years of RITSQ’s existence, we have maintained a website and published data annually, including: news, 4 conferences, 5 courses, 6 posters, 85,362 users, 521,756 sessions, and 283,563 page views. To date, 178 posters have been presented at conferences, seminars, and workshops. Therefore, we ask potential event organizers to kindly send us relevant information in advance so that we can publish, disseminate, and advertise it on our website (https://www.ritsq.org). Collaborators: From México: Drs. P. Escalante, J. Rodríguez, J. Madrigal, M. Canul; and G. López-Orozco. From Chile: Drs. F. Cavieres, B. Schulz, C. Müller, F. Pansetti, S. Zuñiga, E. Benelli; C. Santibañez, L. Bórgell. From Colombia: Dres, N. Patiño, D. Comboriza, L. Peña, P. Acosta, E. Sánchez, J. Tellez, M. Gutiérrez.